Teachers' successful information and communication technology integration in primary school: a Malaysian cultural-historical case study - Razak, Nor Asiah; Ab Jalil, Habibah; Krauss, Steven Eric; Ahmad, Nor Aniza (I G I Global, 2021)
Despite extensive research on ICT integration among teachers, limited knowledge was given to understand ICT's successful integration among teachers. For those purposes, a single-case study aimed to explain the successful integration of ICT by teachers into teaching in one national primary school in Malaysia. Data were collected using a multi-method of data collection, including in-depth interviews, non-participants observations, and document analysis. The results discovered three models that led to teachers' successful ICT integration in teaching, explaining how the interactions between the contradictions, causes of contradictions, and resolutions of contradictions have hindered or influenced the teachers to integrate ICT in their teaching. The findings indicate that the activity system of department and school (prior activities) affecting the classroom activity system (recent activity) led to the successful integration of ICT by teachers in teaching.